Glucose homeostasis and insulin resistance: prevalence, gender differences and predictors in adolescents - Aldhoon-Hainerová, Irena; Zamrazilová, Hana; Dušátková, Lenka; Sedláčková, Barbora; Hlavatý, Petr; Hill, Martin; Hampl, Richard; Kunešová, Marie; Hainer, Vojtěch (Diabetology & metabolic syndrome, 2014)
BACKGROUND: Adolescence, due to transient pubertal insulin resistance (IR), is associated with a higher risk for disturbances of glucose metabolism. The aim of our study was 1) to investigate the prevalence of disturbances of glucose metabolism, 2) to define gender specific homeostasis model assessment of insulin resistance (HOMA-IR) thresholds associated with increased cardiometabolic risks and 3) to provide predictors of HOMA-IR. METHODS: The studied cohort consisted of Czech adolescents aged 13.0-17.9 years: 1,518 individuals of general population and three studied groups according weight category (615 normal weight, 230 overweight and 683 obese). The prevalence of IR, impaired fasting glucose (IFG) and type 2 diabetes was assessed. Risky HOMA-IR thresholds based on components of metabolic syndrome were investigated. HOMA-IR prediction was calculated taking into account age, blood pressure, multiple anthropometric, biochemical and hormonal parameters. RESULTS: In general population cohort, the prevalence of IFG and type 2 diabetes was 7.0% and <0.5%, respectively. Boys regardless of weight presented significantly higher levels of blood glucose and higher prevalence of IFG than girls. Obese boys were found more insulin resistant than obese girls. HOMA-IR thresholds of 3.6 for girls and 4.4 for boys were associated with increased cardiometabolic risks. For both genders, the model of HOMA-IR prediction was composed of age, BMI, ratio of free triiodthyronine to free thyroxine, gamma-glutamyltransferase activity and levels of triglycerides and sex hormone-binding globulin. CONCLUSIONS: The type 2 diabetes in adolescents, including those who were obese, was rarely diagnosed. Obese adolescent boys were at greater risk for IR and for IFG than obese girls. In adolescence, thresholds of HOMA-IR in contrast to predictors were found gender specific.
Keywords: Glucose homeostasis; HOMA-IR prediction; Insulin resistance; Metabolic syndrome; Adolescence; Type 2 diabetes; Obesity